Risk factors of denture stomatitis in diabetes mellitus patients attending Bangbuathong hospital, Nonthaburi province - Settavanit, Daraka (Thai Dental Public Health Journal, 2020)
This cross-sectional analytical study aimed to determine the prevalence and correlation of denture stomatitis among risk factors in 216 removable denture wearers attending non-communicable diseases clinic at Bangbuathong hospital, Nonthaburi province from 2nd October 2017 to 28th September 2018. Data were collected during August - October 2019 by interviewing general and denture information using the structured questionnaire developed for this study then the oral mucosa was examined. The data were analyzed by descriptive statistics; mean, percentage and chi-square. Association between variables was determined by logistic regression analysis at p<0.05 significance. The prevalence of denture stomatitis was 28.7% (type I or pin-point hyperemia 19.1%, type II or diffuse erythema 7.8%, type III or papillary hyperplasia 1.8%). The study variables including gender, patient age, HbA1c level, smoking, type of denture, age of present denture, denture quality, duration of denture wearing, nocturnal denture wearing and denture cleaning were evaluated. The analysis revealed that denture stomatitis was significantly related with duration of denture wearing equal or more than 5 years and nocturnal denture wearing but the association between risk factors and type of denture stomatitis was not found. Dentists should pay attention to patient history taking, oral and denture hygiene instruction including regular check-up for investigating and preventing abnormalities in oral cavity after denture delivery.